Bilateral Traumatic Facial Paralysis with Hearing Impairment and Abducens Palsy - Ouhbi, Imane; Abdellaoui, Taoufik; Errami, Noureddine; Benariba, Fouad (Case Reports in Otolaryngology, 2020)
The temporal bone is often affected in basilar skull fractures. Fractures involving the petrous portion are particularly significant, as they may be associated with neurovascular sequelae. Bilateral facial paralysis secondary to bilateral temporal bone fracture is a rare clinical entity, even more so when associated with other cranial nerve damage such as abducens nerve paralysis and hearing impairment. Only 4 similar cases have been reported in the literature to date. In this paper, we describe a 28-year-old male patient with bilateral facial paralysis, unilateral abducens palsy, and bilateral hearing loss due to bitemporal fractures that developed after a motor vehicle accident. Conservative management was preferred. The 6-month follow-up showed remarkable improvement. This report highlights the effectiveness of conservative management in posttraumatic complete facial and abducens palsy.